A CROSS LOOK AT THE ORGANIZATION'S COMMITMENT TO SOCIAL RESPONSIBILITY. CASE OF A MINING COMPANY IN QUEBEC, CANADA - Marie-Pier CÔTÉ; Doina MURESANU (Annals of the University of Oradea: Economic Science)
This paper presents research results from a larger project, focusing on the study of the links between employees' perceptions of their social identification and the social responsibility management models implemented by their organizations. In this article, we will present the subject of comparative analysis from the perspective of the company and its employees, in relation to the social responsibility management model implemented by the company. The study area for this research is represented by a company in the field of gold mining in the province of Quebec, Canada. Thus, using an exploratory qualitative research method based on the case study, we were able to observe firstly that the integrative model that we designed represents a relevant tool for the analysis of CSR. What's more, the research results showed similarities between the vision of company managers and its employees on CSR, but also divergences, which leads us to conclude that additional efforts should be made by organizations in order to improve their management of social responsibility and make sure it is well known by its employees.